PENGEMBANGAN KARIR PEGAWAI DI BIRO ORGANISASI SEKRETARIAT DAERAH PROVINSI SUMATERA BARAT - YUSRI MARIANI (Jurnal Bahana Manajemen Pendidikan, 2017)
The purpose of this research is to see how the career development of employee’s in Biro Organisasi Sekretariat Daerah Provinsi Sumatera Barat. This is a descriptive research population was 41 people. The research instrument was a questionnaire in the form of Likert Scale, which has proven validity and reliability. The data is processed by using the formula of the average (mean). The results show the career development of employee’s in Biro Organisasi Sekretariat Daerah Provinsi Sumatera Barat quite accomplished with an average score of 3.93.